Islamism in North Africa (ICG Middle East and North Africa Briefing, 2004)
1.: The legacies of history. - Cairo ..., 2004. - 15 S. : Lit.Hinw., Anh. S. 15. - (... ; 20. April 2004).; 2.: Egypt's opportunity. - Cairo ..., 2004. 19 S. : Lit.Hinw. - (... ; 20. April 2004)